A signal denoising method based on goose optimization algorithm for optimal variational modal decomposition and improved wavelet thresholding function - Fang, Lide; Wang, Zhongliang; Sun, Yiqian; Zhu, Zeyu; Sun, Jianzhang; Wang, Mi (Physics of fluids (1994), 2025)
Ultrasonic flowmeters are widely used in energy and control applications, providing accurate and fast measurement of fluid flow rates. This paper proposes a denoising method based on the goose optimization algorithm, a nature-inspired optimization method mimicking the foraging behavior of goose. GO optimizes the penalty factor and decomposition layer number of variational modal decomposition, resulting in the GO-VMD approach. Decomposed modal components are further denoised using an improved wavelet thresholding method. The algorithm is compared with existing methods, such as high-frequency ultrasonic signal processing, and experimental results show that it improves the signal-to-noise ratio by 8%, reduces root mean square error by 5%, retains more useful information, and achieves significant denoising results.